Penyelesaian Sengketa Kewarisan Anak Angkat Yang Memiliki Keterangan Indentitas Sebagai Anak Kandung - Andrizal Andrizal; Mohammad Yusuf Daeng (Fakultas Hukum Universitas Riau, 2023)
Adopted children who have an identity as biological children have the potential to cause inheritance disputes with heir relatives if not resolved through mediation. In Islamic law, the permissibility of adopting a child is limited as long as it is not equated with biological children. This further applies to the civil rights of adopted children including inheritance rights. Adopted children are not entitled to a share of the inheritance and can only get a share based on the obligatory will of their adoptive parents according to the level of the will and not exceeding one-third of the parent's assets. If it exceeds a third of the assets of his parents, then he must obtain the approval of the heirs. On the other hand, the existence of adopted children who have residence documents as biological children has the potential to become a dispute, one of which is the issue of inheritance. In resolving these disputes, mediation as a way of settling cases in a non-litigation process is in principle the first step in efforts to seek law and justice that must be put forward rather than through lawsuits or other law enforcement. This is because in inheritance disputes that occur between adopted children who have residence certificates as biological children have the potential to violate the Population Law and also the Criminal Procedure Code because if it is proven that they intentionally misused population data by providing incorrect information it will lead to actions that can be punishable criminal